International Year of Planet Earth 8. Natural Hazards in Canada - Clague, John; Bobrowsky, Peter (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2010)
SUMMARY Canada, the second largest country in the world, is subject to every hazardous natural process on Earth − large earthquakes, tsunami, volcanic eruptions, landslides, snow avalanches, floods, hurricanes, tornados, severe storms, drought, and sea-level rise. Fortunately, much of the country is sparsely populated; hence risk from these hazardous processes is localized to small areas adjacent to the Canada−US border, where most Canadians live. The greatest risk comes from earthquakes and landslides on the populated south coast of British Columbia and parts of southern Ontario and Québec; from floods in Vancouver, Calgary, Winnipeg, or Toronto; and from hurricanes in Halifax and St. John’s. In the long term, Canada’s coastlines are threatened by sea-level rise and Canada’s northern indigenous peoples are threatened by permafrost thaw caused by global warming.